Sport w szkole i wstrząśnienie mózgu — co należy wiedzieć - Evans, Vicki (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2014)
Every country around the world enjoys some sort of sport. The Olympics sees countries from all over the globe participate in elite sport, in both winter and summer competitions. Australia is widely known for cricket and rugby, America for baseball and gridiron football (amongst others). These sports are played at an elite level as well as beginners from early ages as young as 4yrs in the backyard. Yet it is also these sports that can deliver a ball at the speed of 112km/h (rugby), 105km/h (baseball), 150km/h (cricket) and 211km/h (soccer). This is the same force that a car collision can produce. That force eventually finds a target and in some cases unfortunately, it is a head. Damage to the brain is not only from the impact of the ball hitting its target, rather, the shearing forces of acceleration-deceleration injury that can cause extensive injuries. There has been much discussion of late regarding concussion in sport and the accumulative effects of head blows resulting in varying degrees of memory loss and dementia later in life. The media has been saturated with heightened awareness of chronic traumatic encephalopathy (CTE). This however, is still being researched. It is true that each concussion compounds the one before, but rather than focus on the injury, managers/coaches and sporting codes should be focusing on the identification and proper management of a suspected concussion and the return-to-play protocols. This is especially important in our schools where growing brains need nurturing. This paper will focus on concussion recognition and management in school sport. (JNNN 2014;3(1):31–38)